(untitled) (Ius Novum, 2021)
The article discusses the issue of a parent’s criminal liability for kidnapping or detainment of his/her child. Apart from the general characteristics of the statutory features of the offence, the article analyses the scope of parents’ criminal liability for the act under Article 211 CC depending on the parental power they have. The author discusses this aspect of the perpetra-tors’ behaviour in case they have full parental authority, they do not have parental authority and their parental authority has been limited. Another issue under consideration concerns a family court’s provisional settlement. The article questions the thesis that parents who have full parental authority cannot be perpetrators of the offence under Article 211 CC and can commit that offence only when they have been deprived of their parental power or it has been limited or suspended.